Exploring the Animal Waste Resistome: The Spread of Antimicrobial Resistance Genes Through the Use of Livestock Manure - Checcucci, Alice; Trevisi, Paolo; Luise, Diana; Modesto, Monica; Blasioli, Sonia; Braschi, Ilaria; Mattarelli, Paola (Frontiers in Microbiology, 2020)
Antibiotic resistance is a public health problem of growing concern. Animal manure application to soils is considered among the main causes of propagation and dissemination of antibiotic residues, antibiotic-resistant bacteria (ARB) and antibiotic resistance genes (ARGs) in the soil-water system. In the last decades, studies on the impact of antibiotic contaminated manure on soil microbiome increased exponentially, in particular for taxonomical diversity and ARGs diffusion. ARGs are often located on mobile genetic elements (MGEs). Horizontal transfer of MGEs towards a broad range of bacteria (pathogens and human commensals included) is identified as the main cause for their persistence and dissemination. Chemical and bio-sanitizing treatments reduce the antibiotic load and ARB. Nevertheless, effects of these treatments on the persistence of resistance genes must be carefully considered. This review analyzed the most recent research on antibiotic and ARG environmental dissemination conveyed by livestock waste. Strategies to control ARG dissemination and antibiotic persistence were reviewed with the aim to identify methods for monitoring DNA transferability and environmental conditions promoting such diffusion.